TROPONIN MYOCARDIAL INJURY MARKER AND OUTCOME IN COVID-19: SCOPING REVIEW - Rodrigues, Andreia Aparecida; Cardoso, Joana Darc Chaves; Miraveti, Jocilene de Carvalho; Cenzi, Camila Maria (Cogitare Enfermagem, 2023)
Objective: To analyze scientific evidence on changes in the myocardial injury marker troponin and clinical outcome in patients hospitalized with COVID-19. Method: A scoping review was adopted, in the Medical Literature Analysis and Retrieval System Online, Scientific Electronic Library Online and Virtual Health Library bases, from May to July 2022. Using as descriptors: Troponin; COVID-19; Cardiovascular System. Results: 23 studies revealed cardiac alterations in hospitalized patients with COVID-19 by examining the cardio specific biomarker troponin, in addition to relating it to high mortality rates. Studies have shown a great relationship between acute myocardial injury, evidenced by elevated troponin, and a worse outcome during hospitalization. Conclusion: Cardiovascular changes were mapped in patients hospitalized with COVID -19 who progressed to severe cases of the disease. This study can contribute to care planning through protocols aimed at clinical management, specific for patients with the disease, both in the acute phase and in the post- COVID -19 phase.